SUSTAINABLE REPORTING DAN KINERJA KEUANGAN PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN PROPERTIES DAN REAL ESTATE YANG TERDAFTAR DI ISSI PERIODE 2021-2023) - Hikmaturromadhoniyah Hikmaturromadhoniyah; Kholidiah Kholidiah (CV. Denasya Smart Publisher, 2025)
The purpose of this study is to determine how sustainability reporting affects the net profit of companies in the real estate and property industry listed on the ISSI from 2021 to 2023. A quantitative approach was used in this study. Using the SRDI, which is based on the GRI 2021 requirements, sustainability reporting is evaluated in three main domains: social, environmental, and economic performance. Furthermore, Return on Assets (ROA) serves as an indicator of financial success. A correlation-based quantitative methodology was used in this study. The sample was selected using a purposive selection strategy; after three years of observation, 18 companies were found to meet the requirements. Secondary data for this study came from the website www.idx.co.id. Classical assumption tests and multiple linear regression were used to analyze the data. The results of this study indicate that a company's financial performance is influenced by its economic, environmental, and social performance simultaneously. A corporation's financial success is somewhat influenced by its environmental and social performance, but not by its economic performance.